PENGARUH KUALITAS PELAYANAN (DISTRIBUTIVE JUSTICE, PROCEDURAL JUSTICE, INTERNATIONAL JUSTICE) TERHADAP KEPUASAN NASABAH - Sarida Sirait; Calen Calen (Politeknik Bisnis Indonesia, 2021)
Technological developments are so fast and fast that all banks are increasingly trying to provide excellent service to customers who are the spearhead of the banking business. The high competition in the banking business and the heterogeneous condition of customers make the management have to make efforts to improve services. the inability of banks to deal with customer complaints makes customers dissatisfied and shifting. The large costs associated with service recovery have prevented the banking sector from responding quickly to various customer complaints or customers. The purpose of this study is to determine the extent to which service recovery can improve banking services. The independent variable (independent) in this study is service quality (X), namely the application of service recovery strategies consisting of distributive justice, procedural justice, and interactional justice. Meanwhile, the determining variable (dependent) is customer satisfaction (Y) at Bank BRI Pasar Horas Unit. The analytical technique used in this study is linear regression to see how much influence the variable X has on Y. The results of data processing using SPSS are that X has a significant positive effect on Y with a significance value of 0.00 and a coefficient of determination (R Square) of 0.772. The magnitude of the coefficient of determination of 0.772 is equal to 77.2%, this figure implies that quality affects customer satisfaction by 77.2% Keywords: service quality, customer satisfaction, service recovery